Menumbuhkan Minat Belajar Siswa Dalam Pembelajaran - Imelda Kusuma (Ability: Journal of Education and Social Analysis, 2022)
This study aims to see the students' interest in learning in learning. The results of this study are that interest in learning is one of the components that affect the success of learning. To foster interest in learning in students, we must first pay attention to what is the background that causes a decrease or even loss of interest in learning. After that, we take what steps we should do to foster interest in learning in students. Thus efforts to foster interest in learning in accordance with the target. From the description that has been described above, we can draw several conclusions related to efforts to foster interest in learning in students. First, understand and identify the physical and psychological conditions of students. Second, use various techniques and methods in presenting learning materials. Third, the use of learning media should be able to stimulate students to be interested in participating in learning. Fourth, understand the condition of the family, community, and school environment so that we can find a way out in fostering student interest in learning.